Research on Music Education of “Double Tutor System” for Postgraduate Students in China and Belarus - Leshu Huang,; Grigorieva Olga Nikolaevna, (Journal of Educational Issues, 2024)
The construction of the “double tutor system” is a crucial link in promoting the comprehensive reform of professional master’s degree postgraduate education, and it is also a comprehensive work that involves the interests of primary stakeholders such as universities, enterprises and industry departments, tutors inside and outside the school, and postgraduate students. During the implementation of the “Double Tutor System”, due to the different interest demands of the main stakeholders and the mutual game between them, the contradictions between academic logic and market logic, internal development law of education and external development environment, personal value and social value are typical. Therefore, the Double Tutor of higher education has become the inevitable trend of education development in colleges and universities in today’s society, which is also a new type of school-enterprise joint training mode. A questionnaire survey was conducted for the master’s group as the research target. It also analyzes the relevant questions of the questionnaire, puts forward relevant feasible suggestions, and solves the relevant problems of the double tutor system for postgraduates in China and Belarus, to promote the training path of professional masters and promote the rapid development of new higher education models.